BFGUI: An Interactive Tool for the Synthesis and Analysis of Microphone Array Beamformers - Thomas, Mark; Gamper, Hannes; Tashev, Ivan (Proc. IEEE International Conference on Acoustics, Speech, and Signal Processing (ICASSP), 2016)
Microphone arrays are beneficial for distant speech capture because the signals they capture can be exploited with beamforming to suppress noise and reverberation. The theory for the design and analysis of microphone arrays is well established, however the performance of a microphone array beamformer is often subject to conflicting criteria that need to be assessed manually. This paper describes BFGUI, a interactive graphical tool forMATLAB, for simulating microphone arrays and synthesizing beamformers, and whose parameters can be modified and performance metrics monitored in real-time. Primarily aimed at teaching and research, this tool provides the user with an intuitive insight into the effects of microphone types, number and geometry, and the influence of design constraints such as regularization and white noise gain on derived metrics. The resulting directivity pattern, directivity index and front-back ratio are examples of such metrics. Multiple analytic microphone models are supported and external measured microphone directivity patterns can also be loaded. The designs can be then exported in a variety of formats for processing of real-world data.